THE NEED FOR PROBLEM-BASED LEARNING MEDIA THAT IS ORIENTED TO IMPROVE STUDENTS' MATHEMATICAL LITERACY AND SELF-EFFICACY - Rizky, Muhammad Rafi Fajar; Nurnugroho, Burhanudin Arif; Andriyani, Andriyani (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
Mathematical literacy and student self-efficacy need to be considered because mathematical literacy skills are very important for students to possess and self-efficacy is needed so that students can have confidence in themselves to achieve academic goals. The purpose of this study is to find out what learning media is suitable to be applied to Mathematics Education students, Mercu Buana University Yogyakarta. In addition, this study also aims to determine the level of mathematical literacy and self-efficacy of Mathematics Education students at Mercu Buana University Yogyakarta. The research design used in this study is quantitative descriptive research. Data collection was carried out using questionnaire and test techniques. The instruments used in this study are preliminary study questionnaires, self-efficacy questionnaires, mathematical literacy test questions, The data analysis techniques used in this study are qualitative data analysis with the stages of analysis are: (1) Data Reduction; (2) Data Presentation; and (3) Conclusion Drawn. The procedure for this research includes 3 stages, namely the initial stage, the implementation stage, and the final stage. The results of this study show that there is a need for problem-based learning e-module learning media that is oriented to improve mathematical literacy and student self-efficacy. This can be seen in the results of the study which show that the level of mathematical literacy and self-efficacy still needs to be improved. In addition, students' interest in e-modules is also the basis for students' needs for e-modules. This can illustrate that the e-module is a learning medium that is suitable to be applied to Mathematics Education students, Universitas Mercu Buana Yogyakarta. Suggestions for further research are the need to develop problem-based learning e-modules to improve students' mathematical literacy and self-efficacy